The Mediating Role of Depressive Symptom in Burnout and Career Readiness Relationship: A Study on Arabic Language Learners - Akla Akla; Aguswan Khotibul Umam; Dian Ekawati; Nurkholis Nurkholis (Islamic Guidance and Counseling Journal, 2023)
The present study aimed to investigate the relationship between burnout, career readiness, and depressive symptoms among Arabic language learners in Indonesia. The study used a cross-sectional design and surveyed a sample of Arabic language learners. Results of the study suggest that there is a moderate to low positive correlation between burnout, career readiness, and depressive symptoms, with burnout having a stronger correlation with career readiness and depressive symptoms than career readiness does with depressive symptoms. Additionally, the results suggest that burnout is a significant predictor of career readiness. However, the relationship between burnout and career readiness, through depression, is weak. These findings provide valuable insights into the relationship between burnout, career readiness, and depressive symptoms among Arabic language learners in Indonesia, but it is important to consider the limitations of the study, such as the small sample size, when interpreting the results. Future research should aim to address these limitations in order to gain a more comprehensive understanding of the relationship between these concepts.